Biogas: Strengthening Green Energy Infrastructure for a More Sustainable Future - Mulyono, Yatin; Suranto, Suranto; Yamtinah, Sri; Sarwanto, Sarwanto; Jamil, Abdul (Journal of Biotechnology and Natural Science, 2024)
Biogas has been available as a renewable energy source to accelerate national economic development. This research aimed to analyze the potential of renewable energy production development in Indonesia and present the application of potential waste processing into biogas. This study fills the knowledge gap through a critical review of the potential for developing renewable energy from animal waste in Indonesia, including biogas, power generation, transportation, and value-added chemicals. This study was conducted using a critical review of research articles and is supported by other related literature. The result of the study showed that Indonesia has great potential to develop biogas production due to its substrate availability, particularly from farm animal waste or other organic waste, even though its utilization has not been maximized. The data showed that primary energy consumption, especially in the industrial and transportation sectors, was dominated by fossil fuels and coal. The production of biogas technology development comprehensively included the processes and techniques of waste handling from biogas production. Most of the biogas application approaches were still in the early stage. Identifying opportunities, obstacles, policies, research, and development is still needed, particularly in this relatively new sector.